Active offer of health services in French in Ontario: Analysis of reorganization and management strategies of health-care organizations - Farmanova, Elina; Bonneville, Luc; Bouchard, Louise (The International Journal of Health Planning and Management, 2018)
The availability of health services in French is not only weak but also inexistent in some regions in Canada. As a result, estimated 78% of more than a million of Francophones living in a minority situation in Canada experience difficulties accessing health care in French. To promote the delivery of health services in French, publicly funded organizations are encouraged to take measures to ensure that French-language services are clearly visible, available, easily accessible, and equivalent to the quality of services offered in English. Objective This study examines the reorganization and management strategies taken by health care organizations in Ontario that provide health services in French. Methods Review and analysis of designation plans of a sample of health care organizations. Results Few health care organizations providing services in French have concrete strategies to guarantee availability, visibility, and accessibility of French-language services. Conclusions Implementation of the active offer of French-language services is likely to be difficult and slow. The Ontario government must strengthen collaboration with health care organizations, Francophone communities, and other key actors participating in the designation process to help health care organizations build capacities for the effective offer of French-language services.

Success strategies for linguistically competent healthcare: The magic bullets and cautionary tales of active offer of French-language health services in Ontario - Farmanova, Elina; Bouchard, Louise; Bonneville, Luc (Healthcare Quaterly, 2018)
An active offer of French-language health services (FLHS) was introduced in several Canadian provinces to help create an environment that will anticipate the needs of Francophones in their community and will stimulate the demand for services in French. For the active offer to be implemented, changes in how health services are organized and managed at both organizational and system levels must be introduced. In this perspective paper, we identify several success strategies and potential pitfalls with regards to the implementation of the active offer of FLHS primarily at the level of healthcare organization. Our recommendations are based on a recent health services research study exploring reorganization and management strategies for the delivery of the active offer of FLHS in Ontario and insights from a focus group with healthcare administrators conducted as part of this research. We propose a "wrap-around strategy" called organizational health literacy to help reorient organizational culture and improve management and sustainability of the active offer of FLHS. These strategies have relevance for advocates and professionals working to promote an active offer of FLHS, including healthcare administrators, human resource professionals, quality-improvement specialists and others.

Workload of French-speaking family physicians in Francophone rural and Northern communities in Ontario - Timony, Patrick E.; Gauthier, Alain P.; Sanou, Boroma; Wenghofer, Elizabeth. F. (Canadian Journal of Rural Medicine, 2018)
Introduction: Previous studies have shown that French-speaking family physicians (FSPs) in Ontario are less numerous in areas with high proportions of francophones. The purpose of the current study was to assess whether the degree of concordance between physicians' language of competence and the linguistic profile of the community in which they practise is associated with workload and to explore variations in this relation in rural and northern regions of the province. Methods: This was a secondary analysis of the 2013 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. We analyzed the primary practice location and language of competence of family physicians/general practitioners. We compared the practice characteristics of FSPs and non-French-speaking physicians (NFSPs) by the proportion of the francophone population, geographic location (north vs. south) and community size (urban vs. rural). Results: Data for 10 548 family physician/general practitioners were analyzed. In areas densely populated by francophones, FSPs worked more hours per week on average and had a greater mean number of patient visits than NFSPs. Non-French-speaking physicians working in areas densely populated by francophones had fewer patient visits per hour on average than FSPs. In most cases, the results were particularly accentuated in rural and northern communities. Conclusion: Our findings suggest that, compared to NFSPs, the demands placed on FSPs are disproportionately greater in communities where the need for French-language health care services is greatest and the supply of FSPs is the smallest. Our results underline the importance of properly preparing family physicians to work in areas densely populated by francophones.